THE PERSISTENCE OF THE CONCEPT OF MARI-IT AS A REGULATOR OF ENVIRONMENTAL RESOURCES IN GUIMARAS ISLAND, PHILIPPINES - Harmon S. Recopuerto (International Conference on Social and Islamic Studies, 2021)
Folklore are oral traditions which are commonly told and retold among members of a certain community in the forms of stories, legends, narratives, beliefs, and taboos. This research explores the persistence of the concept of mari-it (literally, “dangerous”) as a regulator of environmental resources in Guimaras Island, Philippines. The research made use of two of the indigenous research methods identified in Sikolohiyang Pilipino as appropriate in Philippine culture. To select the barangays to be the study sites for this research, the indigenous variant of the interview, pakikipagkuwentuhan (“story-telling”) was used. On the other hand, data required for this study was gathered through another indigenous research method, pagtatanong-tanong, a Filipino word which means "asking questions”. This research finds that folklore, particularly the belief in the concept of mari-it, serves as a regulator of natural resources since it limits people’s activities in some areas which are believed to be the dwelling places of spiritual beings. As a result, natural resources in these places remain undisturbed or their exploitation is minimal. It is recommended to make use of these oral traditions to promote ecological consciousness and awareness among people. We can incorporate these oral traditions to our ecological conservation practices that can develop further our environmental management efforts.